Sistem Peringatan Kondisi Jalan Berdasarkan Kecepatan dan Guncangan Sepeda Motor Menggunakan Naive Bayes Berbasis Embedded System - Herwin Yurianda; Dahnial Syauqy; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In developing countries especially Indonesia traffic accidents can result in serious health problems.. Indonesia is a country which ranks fifth in the world in terms of traffic accidents, the data obtained at World Health Organization (WHO). Some of the factors that caused the accident was the road condition, vehicle and rider. However, the riders are often the vehicle outside the limit speed of the spur and the streets are less good is the most dominant factor is the cause of the accident. Based on the issue, it needs to be made to road condition warning system security drive vehicle motorcycle Embedde based System using Naive Bayes method. The sensor used in these systems is the hall effect sensor as the speedometer, and vibration sensors that serve to measure the level of shock two-wheeled vehicle. Will then be classified using Naive Bayes method, with a warning sound output with the use of the buzzer, and the screen display uses LCD, all processed system on an Arduino. Testing conducted include functional testing, system performance and accuracy. From functional testing that has been done, the system has a value of 100% truth, so it can be concluded that this test successfully. For performance testing, the system has a speed of processing time on average by 789.441 p. Whereas on testing Accuracy, the system was tested with test data as much as 43 data and the amount of training data by as much as 86 data and to have the accuracy of 97.76%.